Releasing from Dependence on Research Articles in Health Publications - Heru Santoso Wahito Nugroho; Sanglar Polnok; I Putu Suiraoka; Joel Rey U. Acob; Sahrir Sillehu; Wiwin Martiningsih; Suparji Suparji; Bambang Hadi Sugito (Alliance oh Health Activists (AloHA), 2018)
Until now, most authors in the field of health still publish research articles, even though there are still many types of non-research articles that can be published in scientific journals. In this case it is necessary to understand that in addition to the results of research, the results of critical and innovative thinking are very important to be known by the scientific community. Thus, the authors are expected to learn more about the procedures for writing non-research articles, including examining the specific writing methods that have been determined by each journal. Keywords: Non-research article, scientific publication